Polyvinyl alcohol sponge material as well as preparation method and application thereof

By using the composite technology of corn starch and potato starch in polyvinyl alcohol sponge materials and performing crosslinking and curing treatment, the problem of insufficient mechanical strength and water absorption performance of the material is solved, and efficient semiconductor device cleaning effect is achieved.

CN120137324AInactive Publication Date: 2025-06-13CHANGZHOU XINLING MUGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510241312.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-06-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polyvinyl alcohol sponge materials have low mechanical strength and poor water absorption performance in cleaning and brush shaft applications in the semiconductor industry, making it difficult to meet performance requirements.

Method used

By adding a crosslinking agent and a catalyst to the PVA-starch mixture solution of polyvinyl alcohol, corn starch and potato starch, and then leaving it on stand and heat curing, a polyvinyl alcohol sponge material with high water absorption, fast water absorption rate and high mechanical strength was prepared.

Benefits of technology

The water absorption rate and water absorption rate of polyvinyl alcohol sponge materials are improved, while improving its mechanical strength, which is suitable for efficient cleaning of semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a polyvinyl alcohol sponge material as well as a preparation method and application thereof. The water absorption rate of the polyvinyl alcohol sponge material is greater than or equal to 6.09, the water absorption rate is greater than or equal to 6.99 g / g.min, and the tensile strength is greater than or equal to 0.285 MPa. The polyvinyl alcohol sponge material provided by the invention has the characteristics of high water absorption rate, high water absorption rate and high mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyvinyl alcohol sponge material, a preparation method thereof and an application thereof, and belongs to the field of materials. Background Art

[0002] In the semiconductor industry, very high cleaning conditions are required for fabricating semiconductor devices. For example, when cleaning semiconductor chips, circuit boards and other optical devices, it is necessary to clean the surface impurities thoroughly while not wanting permanent scratches and fine fibers left on the material surface. Based on these problems, we choose the polyvinyl alcohol sponge material widely used in the medical field to make brush shafts, disc brushes and other shapes for cleaning the etched semiconductor materials, and it has been widely recognized in the industry at present.

[0003] The polyvinyl alcohol sponge material has the characteristics of high water absorption rate, softness after saturated water absorption, good resilience, high biocompatibility, good hydrophilicity, etc., and is widely used in the medical field. Since this material also has the advantages of high tensile strength and tear strength, and being durable and wear-resistant, it is also suitable for the preparation of brush shafts in the semiconductor industry.

[0004] In summary, using the polyvinyl alcohol sponge material to prepare the cleaning brush shaft in the semiconductor industry is a technical route with good prospects.

[0005] At the present stage, the polyvinyl alcohol sponge material has the defects of low mechanical strength and poor water absorption performance, and it is difficult to meet the performance requirements of the cleaning brush shaft in the semiconductor industry.

[0006] Therefore, developing a sponge material with relatively high mechanical strength and good water absorption performance for semiconductor cleaning equipment has become the research direction. Summary of the Invention

[0007] The present invention provides a polyvinyl alcohol sponge material, which has the characteristics of high water absorption rate, fast water absorption rate and high mechanical strength.

[0008] The present invention also provides a preparation method of the polyvinyl alcohol sponge material, which has the characteristics of simple process and low cost.

[0009] The present invention also provides a semiconductor device cleaning equipment, which has the characteristic of high cleaning efficiency.

[0010] The present invention provides a polyvinyl alcohol sponge material, wherein the water absorption rate of the polyvinyl alcohol sponge material is greater than or equal to 6.09, the water absorption rate is greater than or equal to 6.99 g / g·min, and the tensile strength is greater than or equal to 0.285 MPa.

[0011] The polyvinyl alcohol sponge material as described above, wherein the porosity of the polyvinyl alcohol sponge material is greater than or equal to 90%, and the apparent density is less than or equal to 0.13 g / cm 3 ; and / or,

[0012] the water absorption rate of the polyvinyl alcohol sponge material is greater than or equal to 10, the water absorption rate is greater than or equal to 32.76 g / g·min, and the tensile strength is greater than or equal to 0.3 MPa.

[0013] The polyvinyl alcohol sponge material as described above, wherein the polyvinyl alcohol sponge material is prepared by a method including the following process:

[0014] 1) A crosslinking agent and a catalyst are successively added to a PVA-starch mixed solution including polyvinyl alcohol, starch and water, and then stirring treatment is carried out to obtain a mixed system;

[0015] 2) The mixed system is successively subjected to static treatment and heat curing treatment to obtain the polyvinyl alcohol sponge material;

[0016] The starch includes corn starch and potato starch;

[0017] The crosslinking agent includes at least one of formaldehyde, glutaraldehyde and glyoxal;

[0018] The catalyst includes at least one of hydrochloric acid and sulfuric acid.

[0019] The present invention also provides a preparation method of a polyvinyl alcohol sponge material. Any of the above polyvinyl alcohol sponge materials can be prepared by using this method. Among them, the method includes the following steps:

[0020] 1) A crosslinking agent and a catalyst are successively added to a PVA-starch mixed solution including polyvinyl alcohol, starch and water, and then stirring treatment is carried out to obtain a mixed system;

[0021] 2) The mixed system is successively subjected to static treatment and heat curing treatment to obtain the polyvinyl alcohol sponge material;

[0022] The starch includes corn starch and potato starch;

[0023] The crosslinking agent includes at least one of formaldehyde, glutaraldehyde and glyoxal;

[0024] The catalyst includes at least one of hydrochloric acid and sulfuric acid.

[0025] In the preparation method of the polyvinyl alcohol sponge material as described above, the mass ratio of the polyvinyl alcohol to the starch is (30:1) to (40:1), and in the starch, the mass ratio of the corn starch to the potato starch is (1:6) to (5:2).

[0026] The preparation method of the polyvinyl alcohol sponge material as described above, wherein step 1) further includes: dissolving the polyvinyl alcohol in water to obtain a polyvinyl alcohol aqueous solution; dissolving the starch in water and then performing ultrasonic treatment to obtain a starch aqueous solution; mixing the polyvinyl alcohol aqueous solution with the starch aqueous solution to obtain the PVA-starch mixed solution.

[0027] The preparation method of the polyvinyl alcohol sponge material as described above, wherein the standing treatment time is 5-10 min.

[0028] The preparation method of the polyvinyl alcohol sponge material as described above, wherein the heat curing treatment temperature is 50-90 °C and the treatment time is 5-20 h.

[0029] The preparation method of the polyvinyl alcohol sponge material as described above, wherein the polyvinyl alcohol is selected from at least one of polyvinyl alcohols with model numbers 1750, 1788, and 1799.

[0030] The present invention also provides a semiconductor device cleaning equipment, which includes any one of the above polyvinyl alcohol sponge materials.

[0031] The polyvinyl alcohol sponge material provided by the present invention has the characteristics of high water absorption rate, fast water absorption rate, and high mechanical strength. Detailed Description of the Invention

[0032] To enable those skilled in the art to better understand the solution of the present invention, the present invention will be further described in detail below. The specific embodiments listed below only describe the principles and features of the present invention, and the examples given are only used to explain the present invention and do not limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts fall within the scope of protection of the present invention.

[0033] The first aspect of the present invention provides a polyvinyl alcohol sponge material, the water absorption rate of this material is greater than or equal to 10, the water absorption rate is greater than or equal to 32.76 g / g·min, and the tensile strength is greater than or equal to 0.3 MPa.

[0034] The polyvinyl alcohol sponge material provided by the present invention is a sponge material prepared by reacting polyethylene with aldehydes. This material has the characteristics of high water absorption rate and water absorption rate, and large tensile strength. This polyvinyl alcohol sponge material can be used to prepare the cleaning brush shaft in the semiconductor industry.

[0035] Furthermore, the polyvinyl alcohol sponge material provided by the present invention has a porosity greater than or equal to 90%, and an apparent density less than or equal to 0.13 g / cm 3Features. The polyvinyl alcohol sponge material with the above characteristics has strong water absorption performance and mechanical strength, and is also relatively light.

[0036] Furthermore, the water absorption rate of the polyvinyl alcohol sponge material is greater than or equal to 10, the water absorption rate is greater than or equal to 32.76 g / g·min, and the tensile strength is greater than or equal to 0.3 MPa. The above materials have higher water absorption rate and water absorption rate, and the characteristics of larger tensile strength are more prominent.

[0037] In one embodiment, the polyvinyl alcohol sponge material provided by the present invention is prepared by a method including the following process:

[0038] 1) Add a crosslinking agent and a catalyst to the PVA-starch mixed solution including polyvinyl alcohol, starch and water in sequence, and then perform a stirring treatment to obtain a mixed system;

[0039] 2) Perform a static treatment and a heat curing treatment on the mixed system in sequence to obtain the polyvinyl alcohol sponge material;

[0040] The starch includes corn starch and potato starch;

[0041] The crosslinking agent includes at least one of formaldehyde, glutaraldehyde and glyoxal;

[0042] The catalyst includes at least one of hydrochloric acid and sulfuric acid.

[0043] Among them, the PVA-starch mixed solution includes polyvinyl alcohol, starch and water. The present invention does not limit the specific preparation method of the PVA-starch mixed solution, and it only needs to meet the requirement of including polyvinyl alcohol, starch and water. Furthermore, the present invention does not limit the mass ratio of polyvinyl alcohol, starch and water in the PVA-starch mixed solution, and the commonly used mass ratio in the art can be used.

[0044] Among them, the starch includes corn starch and potato starch at the same time. The present invention does not limit the mass ratio of the two starches, and it only needs to meet the requirement of including the two starches at the same time.

[0045] The role of the crosslinking agent is to react with polyvinyl alcohol, and the catalyst is used to catalyze the reaction between the crosslinking agent and polyvinyl alcohol. The present invention does not limit the addition ratio of polyvinyl alcohol, catalyst and crosslinking agent, and the common ratio in the art can be used as long as the polyvinyl alcohol sponge material can be prepared. Adding a crosslinking agent and a catalyst to the PVA-starch mixed solution obtains a mixed system. Among them, adding the crosslinking agent first and then the catalyst can prevent sulfuric acid from carbonizing the starch, and adding the crosslinking agent first and then the catalyst can well improve this situation.

[0046] Furthermore, static treatment of the mixed system can eliminate physical bubbles in the mixed solution. The product obtained by static treatment is subjected to heat curing treatment. During the heat curing treatment, polyvinyl alcohol and the crosslinking agent react under the action of the catalyst to form a polyvinyl alcohol sponge material. Among them, corn starch and potato starch are used as pore-forming agents to form pores in the polyvinyl alcohol sponge material.

[0047] Furthermore, in one embodiment, after the heat curing treatment is completed, it further includes washing the obtained product to neutrality, aiming to remove impurities such as starch contained in the product, so as to obtain the polyvinyl alcohol sponge material provided by the present invention.

[0048] The inventors found that the polyvinyl alcohol sponge material prepared by the above method has the characteristics of high water absorption rate, fast water absorption rate, and high strength and hardness in the wet state. The inventors speculate that the reason may be that when using corn starch alone, the pores in the prepared polyvinyl alcohol sponge material are small and prone to agglomeration and defects; when using potato starch alone, although the pores in the prepared polyvinyl alcohol sponge material are large and the water absorption rate is high, the mechanical strength is low. When the two starches are compounded as pore-forming agents, the characteristics of good strength and hardness in the wet state, high overall strength, and delicate surface of the sample prepared with corn starch can be fully utilized, and the characteristics of large pores and high water absorption rate of the sample prepared with potato starch can also be utilized, so that the prepared polyvinyl alcohol sponge material has the characteristics of high water absorption rate, fast water absorption rate, and high strength and hardness in the wet state.

[0049] The second aspect of the present invention provides a preparation method of a polyvinyl alcohol sponge material. Using this method, any polyvinyl alcohol sponge material provided by the first aspect of the present invention can be prepared. The preparation method includes the following steps:

[0050] 1) Add a crosslinking agent and a catalyst to the PVA-starch mixed solution including polyvinyl alcohol, starch and water in sequence, and then carry out stirring treatment to obtain a mixed system;

[0051] 2) Carry out static treatment and heat curing treatment on the mixed system in sequence to obtain a polyvinyl alcohol sponge material;

[0052] The starch includes corn starch and potato starch;

[0053] The crosslinking agent includes at least one of formaldehyde, glutaraldehyde, and glyoxal;

[0054] The catalyst includes at least one of hydrochloric acid (mass concentration: 36%-38%) and sulfuric acid (mass concentration: 95%-98%).

[0055] Among them, the meanings of the PVA-starch mixed solution, static treatment, heat curing treatment, starch, crosslinking agent, and catalyst are the same as those above, and will not be elaborated here.

[0056] The inventors found that the polyvinyl alcohol sponge material prepared by the above method has the characteristics of high water absorption rate, fast water absorption rate, and high strength and hardness in the wet state. The inventors speculated that the reason may be that the method uses a compound of corn starch and potato starch as a pore-forming agent, which can not only give full play to the characteristics of corn starch samples with good strength and hardness in the wet state, high overall strength, and delicate surface, but also give play to the characteristics of potato starch samples with large pores and high water absorption rate. Therefore, the polyvinyl alcohol sponge material prepared by this method has the characteristics of high water absorption rate, fast water absorption rate, and high strength and hardness in the wet state. Further, this method can prepare a polyvinyl alcohol sponge material with excellent performance using common raw materials, and has the characteristic of low preparation cost.

[0057] Further, in one embodiment, the mass ratio of polyvinyl alcohol to starch in the PVA-starch mixed solution is 30:1 to 40:1. Controlling the appropriate mass ratio of polyvinyl alcohol to starch can endow the polyvinyl alcohol sponge material with high water absorption and high porosity through the principle of formaldehyde condensation.

[0058] Further, in one embodiment, the mass ratio of corn starch to potato starch is 1:6 to 5:2. Controlling the appropriate mass ratio of corn starch to potato starch can achieve the technical effects of high water absorption rate and high strength products through the principles of high strength and good elasticity in the wet state of corn starch products and high porosity, high water absorption rate, and no agglomeration of potato starch products.

[0059] In one embodiment, step 1) further includes: dissolving polyvinyl alcohol in water to obtain a polyvinyl alcohol aqueous solution; dissolving starch in water and then performing ultrasonic treatment to obtain a starch aqueous solution; mixing the polyvinyl alcohol aqueous solution and the starch aqueous solution to obtain a PVA-starch mixed solution.

[0060] Among them, ultrasonic treatment after dissolving starch in water can achieve the technical effect of uniform pores in the product through the principle of ultrasonic dispersion.

[0061] Further, in one embodiment, in the polyvinyl alcohol aqueous solution, the mass ratio of polyvinyl alcohol to water is 1:5 to 1:9. Controlling the appropriate mass ratio of polyvinyl alcohol to water can make the prepared product have a larger porosity and the product will not show delamination.

[0062] Further, in one embodiment, controlling the standing treatment time to be 5-10 min can eliminate physical bubbles in the mixed system.

[0063] In one embodiment, the treatment temperature of the heat curing treatment is 50-90 °C, and the treatment time is 5-20 h. Controlling the heat curing treatment temperature within the above range can increase the reaction rate of polyvinyl alcohol and the cross-linking agent, making the preparation method of the polyvinyl alcohol sponge material provided by the present invention more efficient.

[0064] Further, in one embodiment, the polyvinyl alcohol is selected from at least one of polyvinyl alcohols of models 1750, 1788, and 1799. Due to their hydrophilic properties, the above-mentioned models of polyvinyl alcohol can achieve the technical effects of water absorption and skeleton support for pores when used to prepare polyvinyl alcohol sponge materials.

[0065] The third aspect of the present invention provides a semiconductor device cleaning equipment, which includes the polyvinyl alcohol sponge material provided by the first aspect of the present invention. Since the polyvinyl alcohol sponge material provided by the present invention has the characteristics of high water absorption rate, fast water absorption rate, and high strength and hardness in the wet state, the semiconductor device cleaning equipment has the characteristic of high cleaning efficiency.

[0066] Hereinafter, the polyvinyl alcohol sponge material provided by the present invention, its preparation method and application will be introduced in detail with specific examples.

[0067] Example 1

[0068] The following method is used to prepare the polyvinyl alcohol sponge material in this example:

[0069] 1) Weigh 250 g of polyvinyl alcohol and put it into a three-necked flask, then add 1500 g of water, heat and stir to obtain a polyvinyl alcohol (1:6) solution;

[0070] Weigh 5 g of corn starch and 2 g of potato starch, put them into a beaker, add 23 ml of water, stir at a speed of 350 rad / min for 5 min, and ultrasonically disperse for 10 min to obtain a starch solution;

[0071] 2) Take 30 g of the polyvinyl alcohol solution, mix the polyvinyl alcohol solution and the starch solution to obtain a PVA-starch mixed solution;

[0072] 3) Add 4 g of glutaraldehyde and 2 g of sulfuric acid with a mass fraction of 98% to the mixed solution in sequence, stir at a speed of 350 rad / min for 10 min to obtain a mixed solution;

[0073] 4) After high-speed stirring the mixed solution, pour it into a mold and let it stand for 10 min, then put it into an oven and heat at 70°C for 18 h for curing;

[0074] 5) After the curing is completed, wash the sample to neutral to obtain the polyvinyl alcohol sponge material A1.

[0075] Example 2

[0076] The following method is used to prepare the polyvinyl alcohol sponge material in this example:

[0077] 1) Weigh 250 g of polyvinyl alcohol and put it into a three-necked flask, then add 1250 g of water, heat up and stir to obtain a polyvinyl alcohol (1:5) solution;

[0078] Weigh 3 g of corn starch and 4 g of potato starch, put them into a beaker, add 23 g of water, stir and disperse ultrasonically to obtain a starch solution;

[0079] 2) Take 30 g of the polyvinyl alcohol solution, mix the polyvinyl alcohol solution and the starch solution together to obtain a PVA-starch mixed solution;

[0080] 3) Add 6 g of formaldehyde and 2 g of hydrochloric acid with a mass fraction of 37% to the mixed solution in sequence, and stir at high speed to obtain a mixed solution;

[0081] 4) After stirring the mixed solution at high speed, pour it into a mold and let it stand for 10 min, then put it into an oven and heat at 65 °C for 15 h for curing;

[0082] 5) After curing is completed, wash the sample until it is neutral to obtain polyvinyl alcohol sponge material A2.

[0083] Example 3

[0084] This example uses the following method to prepare polyvinyl alcohol sponge material:

[0085] 1) Weigh 250 g of polyvinyl alcohol and put it into a three-necked flask, then add 2000 g of water, heat up and stir to obtain a polyvinyl alcohol (1:8) solution;

[0086] Weigh 2 g of corn starch and 5 g of potato starch, put them into a beaker, add 28 g of water, stir and disperse ultrasonically to obtain a starch solution;

[0087] 2) Take 30 g of the polyvinyl alcohol solution, mix the polyvinyl alcohol solution and the starch solution together to obtain a PVA-starch mixed solution;

[0088] 3) Add 6 g of formaldehyde and 3 g of sulfuric acid with a mass fraction of 98% to the mixed solution in sequence, and stir at high speed to obtain a mixed solution;

[0089] 4) After stirring the mixed solution at high speed, pour it into a mold and let it stand for 10 min, then put it into an oven and heat at 65 °C for 12 h for curing;

[0090] 5) After curing is completed, wash the sample until it is neutral to obtain polyvinyl alcohol sponge material A3.

[0091] Example 4

[0092] This example uses the following method to prepare polyvinyl alcohol sponge material:

[0093] 1) Weigh 250 g of polyvinyl alcohol and put it into a three-necked flask, then add 1750 g of water. Heat it up and stir to obtain a polyvinyl alcohol (1:7) solution;

[0094] Weigh 2 g of corn starch and 6 g of potato starch, put them into a beaker, add 30 g of water, stir and disperse ultrasonically to obtain a starch solution;

[0095] 2) Take 30 g of the polyvinyl alcohol solution, mix the polyvinyl alcohol solution and the starch solution together to obtain a PVA-starch mixed solution;

[0096] 3) Add 4 g of glyoxal and 5 g of sulfuric acid with a mass fraction of 98% to the mixed solution in sequence, and stir at high speed to obtain a mixed solution;

[0097] 4) After stirring the mixed solution at high speed, pour it into a mold and let it stand for 10 min, then put it into an oven and heat at 70 °C for 20 h to cure;

[0098] 5) After curing, wash the sample until it is neutral to obtain polyvinyl alcohol sponge material A4.

[0099] Example 5

[0100] The following method is used to prepare polyvinyl alcohol sponge material in this example:

[0101] 1) Weigh 250 g of polyvinyl alcohol and put it into a three-necked flask, then add 1500 g of water. Heat it up and stir to obtain a polyvinyl alcohol (1:6) solution;

[0102] Weigh 1 g of corn starch and 6 g of potato starch, put them into a beaker, add 20 g of water, stir and disperse ultrasonically to obtain a starch solution;

[0103] 2) Take 30 g of the polyvinyl alcohol solution, mix the polyvinyl alcohol solution and the starch solution together to obtain a PVA-starch mixed solution;

[0104] 3) Add 2 g of formaldehyde and 2 g of hydrochloric acid with a mass fraction of 37% to the mixed solution in sequence, and stir at high speed to obtain a mixed solution;

[0105] 4) After stirring the mixed solution at high speed, pour it into a mold and let it stand for 10 min, then put it into an oven and heat at 75 °C for 13 h to cure;

[0106] 5) After curing, wash the sample until it is neutral to obtain polyvinyl alcohol sponge material A5.

[0107] Comparative Example 1

[0108] The following method is used to prepare polyvinyl alcohol sponge material in this comparative example:

[0109] 1) Weigh 250 g of polyvinyl alcohol and put it into a three-necked flask, then add 1500 g of water. Heat it up and stir to obtain a polyvinyl alcohol (1:6) solution;

[0110] Weigh 7 g of corn starch and put it into a beaker, add 23 ml of water, stir and disperse it ultrasonically to obtain a starch solution;

[0111] 2) Take 30 g of the polyvinyl alcohol solution, mix the polyvinyl alcohol solution and the starch solution together to obtain a PVA-starch mixed solution;

[0112] 3) Add 4 g of formaldehyde and 2 g of sulfuric acid with a mass fraction of 98% to the PVA-starch mixed solution in sequence, and stir at high speed to obtain a mixed solution;

[0113] 4) Pour the mixed solution into a mold after stirring at high speed, let it stand for 10 min, and put it into an oven at 70 °C for heating and curing for 16 h;

[0114] 5) After the curing is completed, wash the sample until it is neutral to obtain the polyvinyl alcohol sponge material B1.

[0115] Comparative Example 2

[0116] The following method is used to prepare the polyvinyl alcohol sponge material in this comparative example:

[0117] 1) Weigh 250 g of polyvinyl alcohol and put it into a three-necked flask, then add 1500 g of water. Heat it up and stir to obtain a polyvinyl alcohol (1:6) solution;

[0118] Weigh 7 g of potato starch and put it into a beaker, add 20 g of water, stir and disperse it ultrasonically to obtain a starch solution;

[0119] 2) Take 30 g of the polyvinyl alcohol solution, mix the polyvinyl alcohol solution and the starch solution together to obtain a PVA-starch mixed solution;

[0120] 3) Add 3 g of formaldehyde and 2 g of sulfuric acid with a mass fraction of 98% to the mixed solution in sequence, and stir at high speed to obtain a mixed solution;

[0121] 4) Pour the mixed solution into a mold after stirring at high speed, let it stand for 10 min, and put it into an oven at 70 °C for heating and curing for 12 h;

[0122] 5) After the curing is completed, wash the sample until it is neutral to obtain the polyvinyl alcohol sponge material B2.

[0123] Test Example

[0124] (1) Test of the apparent density of the material

[0125] According to GB / T 6343-1995, the calculation method is as follows:

[0126] ρ = m / v

[0127] Where m refers to the mass of the sample after drying, V refers to the volume of the sample, and ρ refers to the apparent density of the polyvinyl formal foaming material.

[0128] (2)Mechanical property test

[0129] Use an AI-3000 universal material tensile machine to test the tensile strength according to the GBT528-1998 standard, test the stress-strain curve of the material. During the test, the distance between the clamps is 2 mm, set the extensometer clamp rate to 500 mm / min, and record the elastic modulus value obtained by the instrument after the test. Process the data through Origin to obtain the stress-strain curve, and obtain the toughness value of the material through the integral area of the curve and the coordinate.

[0130] (3)Water absorption rate

[0131] According to the standard SG-232-81 of the Ministry of Light Industry, calculate the water absorption rate according to the following formula:

[0132] X=(G 2 -G 1 ) / G 1

[0133] In the formula, G 1 is the weight of the sponge brush before water absorption, and G 2 is the weight of the sponge brush after water absorption.

[0134] (4)Porosity

[0135] Calculate according to the following formula:

[0136]

[0137] Where P is the porosity, Vt is the total volume of the sample, ρ is the density of the sample after drying, and m is the mass of the sample after drying.

[0138] (5)Water absorption rate

[0139] Calculate according to the following formula:

[0140] Water absorption rate = (G 2 -G 1 ) / (t×G 1 )

[0141] In the formula, G 1 is the weight of the sponge brush before water absorption (g), G 2 is the weight of the sponge brush after water absorption (g), and t is the water absorption time, unit: g / g·min.

[0142] The properties of the sponge materials prepared in each example and comparative example were tested respectively according to the above test methods, and the data are shown in Table 1:

[0143] Table 1

[0144]

[0145] As can be seen from Table 1, firstly, the tensile strength of samples A1 - A5 is significantly higher than that of samples B1 and B2; secondly, although sample B2 has a similar water absorption rate to samples A1 and A5, the strength of samples A1 and A5 is significantly higher than that of B2, which indicates that the composite starch can be used to prepare samples with both water absorption performance and strength. Further, when the mass ratio of corn starch to potato starch is 1:6 and 5:2, the comprehensive performance of the prepared samples is better.

[0146] Finally, it should be noted that: the above examples are only used to illustrate the technical solutions of the present invention, and are not intended to limit it; although the present invention has been described in detail with reference to the foregoing examples and comparative examples, those of ordinary skill in the art should understand that: they can still modify the technical solutions described in the foregoing examples, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polyvinyl alcohol sponge material, characterized in that: The water absorption rate of the polyvinyl alcohol sponge material is greater than or equal to 6.09, the water absorption rate is greater than or equal to 6.99 g / g·min, and the tensile strength is greater than or equal to 0.285 MPa.

2. The polyvinyl alcohol sponge material according to claim 1, characterized in that: The porosity of the polyvinyl alcohol sponge material is greater than or equal to 90%, and the apparent density is less than or equal to 0.13 g / cm 3 and / or, The water absorption rate of the polyvinyl alcohol sponge material is greater than or equal to 10, the water absorption rate is greater than or equal to 32.76 g / g·min, and the tensile strength is greater than or equal to 0.3 MPa.

3. The polyvinyl alcohol sponge material according to claim 1 or 2, characterized in that: The polyvinyl alcohol sponge material is prepared by a method comprising the following steps: 1) adding a crosslinking agent and a catalyst to a PVA-starch mixed solution including polyvinyl alcohol, starch and water in sequence and stirring the mixture to obtain a mixed system; 2) sequentially subjecting the mixed system to a static treatment and a heating and curing treatment to obtain the polyvinyl alcohol sponge material; The starch includes corn starch and potato starch; The cross-linking agent includes at least one of formaldehyde, glutaraldehyde and glyoxal; The catalyst includes at least one of hydrochloric acid and sulfuric acid.

4. A method for preparing the polyvinyl alcohol sponge material according to any one of claims 1 to 3, characterized in that: The steps include: 1) adding a crosslinking agent and a catalyst to a PVA-starch mixed solution including polyvinyl alcohol, starch and water in sequence and stirring the mixture to obtain a mixed system; 2) sequentially subjecting the mixed system to a static treatment and a heating and curing treatment to obtain the polyvinyl alcohol sponge material; The starch includes corn starch and potato starch; The cross-linking agent includes at least one of formaldehyde, glutaraldehyde and glyoxal; The catalyst includes at least one of hydrochloric acid and sulfuric acid.

5. The method for preparing the polyvinyl alcohol sponge material according to claim 4, characterized in that: The mass ratio of the polyvinyl alcohol to the starch is (30:1) to (40:1), and in the starch, the mass ratio of the corn starch to the potato starch is (1:6) to (5:2).

6. The method for preparing the polyvinyl alcohol sponge material according to claim 5, characterized in that: Step 1) also includes: dissolving the polyvinyl alcohol in water to obtain a polyvinyl alcohol aqueous solution; dissolving the starch in water and then performing ultrasonic treatment to obtain a starch aqueous solution; mixing the polyvinyl alcohol aqueous solution with the starch aqueous solution to obtain the PVA-starch mixed solution.

7. The method for preparing the polyvinyl alcohol sponge material according to claim 6, characterized in that: The treatment time of the static treatment is 5-10 min.

8. The method for preparing the polyvinyl alcohol sponge material according to claim 7, characterized in that: The treatment temperature of the heating and curing treatment is 50-90° C., and the treatment time is 5-20 h.

9. The method for preparing a polyvinyl alcohol sponge material according to any one of claims 4 to 8, characterized in that: The polyvinyl alcohol is selected from at least one of polyvinyl alcohols with models 1750, 1788 and 1799.

10. A semiconductor device cleaning device, characterized in that: The invention comprises the polyvinyl alcohol sponge material according to any one of claims 1 to 3.